The Pursuit of COVID-19 Biomarkers: Putting the Spotlight on ACE2 and TMPRSS2 Regulatory Sequences - Barash, Ayelet; Machluf, Yossy; Ariel, Ilana; Dekel, Yaron (Frontiers in Medicine, 2020)
Diverse populations worldwide are differentially affected by Corona virus disease 2019 (COVID-19), while socio-economic background has been studied extensively, little is known about the genetic variation underlying this phenomenon. This study is aimed at examining the genetic basis behind the discrepancies among diverse ethnic groups in terms of COVID-19 susceptibility for viral infection, disease prognosis and mortality. To this end, in silico analysis of single nucleotide polymorphic sites (SNPs) within regulatory sequences of the human angiotensin-converting enzyme 2 (ACE2) and transmembrane protease serine 2 (TMPRSS2) – the virus' gateway to host cells - and their plausible implications on expression levels was conducted. Variations in the human ACE2 and TMPRSS2 regulatory sequences are likely to be involved in and contribute to this phenomenon. SNPs which are abundant in the more susceptible populations introduce binding sites for transcription factors or they may invalidate BSs for transcription repressor - both may enhance target genes (ACE2 or TMPRSS2) expression in the relevant target tissues. SNPs which are abundant in the more resistant populations may invalidate BSs for a transcriptional repressor, or they may introduce BSs for a transcriptional repressor or initiator of mRNA degradation which may reduce target genes expression levels. This aspect, when added to the socio-economic factors, can be a cause for the divergent prevalence of the disease, and the different mortality rates within diverse populations. This demonstration may call for a shift in the paradigm of searching for COVID-19 biomarkers, such that SNPs within regulatory sequences should be of high importance.